Is Exchange Rate Stabilization an Appropriate Cure for the Dutch Disease? - Medina Guzman, Juan Pablo (IMF Working Papers; Working Paper ;, 2010)
This paper evaluates how successful is a policy of exchange rate stabilization to counteract the negative effects of a Dutch Disease episode. We consider a small open economy model that incorporates nominal rigidities and a learning-by-doing externality in the tradable sector. The paper shows that leaning against an appreciated exchange rate can prevent an inefficient loss of tradable output but at the cost of generating a misallocation of resources in other sectors of the economy. The paper also finds that welfare is a decreasing function of exchange rate intervention. These results suggest that stabilizing the nominal exchange rate in response to a Dutch Disease episode is highly distortionary.